The effects of selection attributes of café on revisit intention: a conceptual study - Chin, Jin Bui; Toh, Pei Sung; Ang, Hong Loong (Penerbit Universiti Malaysia Sabah, 2024)
The objective of this study is to examine the effects of selection attributes of cafe on revisit intention in Malaysia. The cafe industry in Malaysia has undergone significant growth driven by factors such as urbanization, rising disposable incomes, and a growing appreciation for specialty coffee. As a result, there have been expansion and diversification, mirroring global trends in the food and beverage sector. In light of the expanding numbers of cafe and the growing desire for unique culinary experiences, customers have more choices whereby their intention to revisit the same cafe might be affected. Therefore, this paper attempts to explore the factors that influence on revisit intention among customers of cafe in Sabah, Malaysia. Some of the issues being highlighted in the literature previously associated with the cafe industry in Malaysia are related to unpleasant customer experience, pricing and value perception misalignment, lack of accessibility and convenience.Thus, this paper discusses the main problems faced by cafe in Sabah related to the factors that effect on revisit intention of customers.